PENERAPAN UNSUR-UNSUR ARSITEKTUR TRADISIONAL JAWA PADA INTERIOR PUBLIC SPACE DI SURAKARTA - Joko Budiwiyanto (Institut Seni Indonesia Surakarta, 2009)
This article represents observation result towards traditional architecture elements of Java on public space interior in Surakarta. Observation is carried out to the public buildings as a hotel, museum, restaurant, office, etc. It can be found from the observation that there are some public buildings in Surakarta which adopted the traditional architecture elements of Java as room shaping element and aesthetic element in creating room interior nuance of Javanese style.Keyword : application, traditional, architecture, Java, interior